Morgagni’s Diaphragmatic Hernia with Large ASD Secondum and Sever PHT Mimicking a Severe Congenital Heart Disease in a Newborn and Cause Delayed Diagnosis of Morgagni’s Diaphragmatic Hernia: A Case Report - Khaleel, Huda (Archives of Clinical and Medical Case Reports, 2022)
Morgagni hernia is a rare diaphragmatic hernia usually due to congenital defects in the diaphragm. It is rarely associated with cardiac anomalies, most commonly atrial small (ostium secundum) or ventricular septal defects. We report a rare case of Morgagni hernia occurring in association with Large ASD Secondum and Sever PHT mimicking a severe congenital heart disease in a newborn and the lack of awareness of the delayed presentation of Morgagni’s diaphragmatic hernia cause delayed of diagnosis. Clinical Discussion: Our patients, a one-month-old girl, present with cyanosis and shortness of breath admitted were admitted with complaints of chronic cough and repeated chest infections treated accordingly and discharge in good condition. Readmitted after 1 week with similar presentation but her symptoms get worse by time ,patient admitted to PICU as aspiration Pneumonia, patient during the admission diagnosed with Congenital heart disease large ASD (ostium secundum) and Sever PHT, by echocardiography .she was still lethargic hypotonic, low birth weight , she had intermittent cyanosis inspit treating the chest infection was investigated, thoroughly later she was diagnosed with Morgagni Hernia after repeating CT chest with contrast two times. Repair of hernia was done and outcome was good inspite she was diagnosed late at age of 2 years. pulmonary hypertention treated ASD closure by double device. Conclusion: Morgagni’s CDH is a rare malformation, which is difficult to diagnose by even the most experienced physicians. • Compression of the heart by the bowel might have led to the incorrect diagnosis of congenital heart disease. Even in this era of highly sophisticated diagnostic tools, • The basic idea of reporting this case is its rarity in in